The characterization of oxide based ceramic coating synthesized on Al-Si binary alloys by microarc oxidation - Gulec, Ali Emre; Gencer, Yücel; Tarakçı, Mehmet (Elsevier Science Sa, 2015)
The Al-Si binary alloys were prepared in an atmosphere controlled furnace with the addition of 1, 2, 4, 8, 12, 16 and 32 at.% Si. The alloys were coated by microarc oxidation process for 120 min in a basic electrolyte containing silicate. X-Ray Diffraction, scanning electron microscope-energy dispersive X-ray spectroscopy, profilometry and Vickers microhardness tester were employed for the characterization of the coatings. The coating thickness, average microhardness and surface roughness decreased with an increase of Si content in the substrates. alpha-Al2O3 phase was formed in the inner region of the coating of Al-Si alloys with 1-2 at.% Si while all coatings were composed of mullite and gamma-Al2O3 phases along with the amorphous phase. The coating surface became smoother, the glassy regions and number of porosities with finer sizes increased with the increase of Si content in the alloys. The Si concentration was relatively higher at the most outer and inner regions of the coating and it was approximately constant in the other parts of the coatings. The entrapped volume of porosities in the coatings increased with the Si content of the substrates. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Microarc oxidation (MAO); Ceramic coating; Al-Si alloys; Alumina; Oxide based coating